EFEKTIVITAS PROGRAM GERAKAN INDONESIA SADAR ADMINISTRASI DALAM PENGADAAN DOKUMEN KEPENDUDUKAN DI KOTA PEKANBARU - Povi Nasari; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Povi Nasari, Effectiveness Of The administration-aware indonesian movement Program In The procurement Of Population documents in the Of Pekanbaru City. Supervised by the Mr.Zulkarnaini. The purpose of this study is to analyze the effectiveness of the GISA program in the procurement of population documents at the Pekanbaru City Population and Civil Registration Office and to analyze the factors that hinder the achievement of the effectiveness of the GISA program in the procurement of population documents. Descriptive research method with a qualitative approach. The results of this study indicate that the effectiveness of the GISA program has been achieved while the inhibiting factors for the success of the GISA program are: 1) Program socialization is not optimal, and 2) Lack of public knowledge in using the Pekanbaru City Disdukcapil website. Suggestions put forward to support the success of the program are that the Department of Population and Civil Registration of Pekanbaru City be more proactive in disseminating the GISA program and good cooperation between stakeholders to support the GISA program. Keywords: Effectiveness, GISA Program, Population Documents.